To construct a polynomial function based on the given zeros and multiplicities, we start with the zeros and their associated multiplicities:
- Zero at \( x = 4 \) with multiplicity 1 means we include the factor \( (x - 4) \).
- Zero at \( x = -2 \) with multiplicity 3 means we include the factor \( (x + 2)^3 \).
Combining these factors, the polynomial function \( f(x) \) can be expressed as:
\[ f(x) = (x - 4)(x + 2)^3 \]
The correct response from the provided options is:
\[ f(x) = (x - 4)(x + 2)^3 \]